Cattle manure and inorganic nitrogen fertilizer application effects on soil hydraulic properties and maize yield of two soils of Murewa district, Zimbabwe - Dunjana, N; Nyamugafata, P; Nyamangara, Justice; Mango, Nelson (Wiley, 2014)
This study set out to determine the effects of cattle manure and inorganic N‐fertilizer application on the hydraulic properties and maize yield of a clay and sandy soil in a smallholder farming area of Zimbabwe. Four fields classified as homefields (HF: more fertile and closer to homesteads) and outfields (OF: less fertile and further from the homesteads) were selected on clay and sandy soil. They were subjected to four treatments, control (no fertility amendment), 5, 15 and 25 t/ha cattle manure + 100 kg/ha N (as ammonium nitrate) for 7 years. A two‐way randomized complete block design was used with fertility and field type as the two factors. Clay soil hydraulic properties, which included density of macropores with a diameter >300 μm, unsaturated hydraulic conductivity, steady‐state infiltration rate, moisture retention under low suction and maize grain yield, were significantly improved (P < 0.05) by fertility management compared with the control and were generally comparable between the HF and OF. Fertility management significantly improved maize grain yield on sandy soils but did not enhance hydraulic parameters, thereby indicating poor responsiveness in structural build‐up. On the other hand, significantly different hydraulic parameters between the sandy soil HF and OF suggested effects of other factors not related to soil fertility and field type treatments. We therefore concluded that application of a high rate (25 t/ha) of cattle manure and inorganic N‐fertilizer is beneficial for fertility restoration to the degraded OFs with associated comparable hydraulic properties on HFs and OFs on clay soil, unlike on sandy soil.